PENGADILAN HAK ASASI MANUSIA SEBAGAI UPAYA PERTAMA DAN TERAKHIR DALAM PENYELESAIAN PELANGGARAN BERAT HAK ASASI MANUSIA DI TINGKAT NASIONAL - Lina Hastuti (Faculty of Law, Universitas Jenderal Soedirman, 2012)
This article is to examine national courts as a forum first and final settlement of the case enforcement as a gross violation of human rights and that mechanism. Research that is theoretical research, encourage a fuller understanding of the conceptual basis of the principles of law and the process of finding the rule of law, legal principles and legal doctrines in order to answer the legal issues at hand. Based on Presidential Decree No. 53 of 2001 and Act No. 26 of 2004 established an ad hoc human rights court in East Timor, to prosecute accused perpetrators responsible for gross human rights abuses in East Timor after the popular consultation in 1999 and the results are very far from expectations. The cause of the failure of the judicial process can be grouped in the legal and non-legal factors. Legal factors are many weaknesses Act No. 26 of 2004. In addition, law enforcement officers are not credible, so that the resulting decisions do not fulfil international standards as an impartial tribunal and sense of fairness to all parties. While the non-legal factors associated with the political aspects, such as perceived political will is lacking. National mechanisms should be the first and last attempt to resolve as a gross violation of human rights, so there will be no interference from the international court because of the inability and unwillingness of Indonesia. Key words : gross human rights violations, law enforcement, national mechanism